Size and determinants of leverage : comparative analysis of shariah and non-shariah complaint firms classified as financially distressed in Malaysia / Nur Imanina Zulyadzri - Zulyadzri, Nur Imanina (2020)
This research examines the determinants of leverage which is comparative analysis of Shariah and non-Shariah compliant firms classified as financially distressed in Malaysia. Total debts divided by total assets is used as a proxy for leverage. Five factors frequently employed in previous research were used in this research. The factors were used in this research which are growth opportunity, tangibility, liquidity, profitability and firm’s size. The target population of this research was Shariah and non-Shariah compliant firms classified as financially distressed in Malaysia by Bursa Malaysia under requirement of Practice Note 17 (PN17). Data used in this research were secondary data. The data was collecting using DataStream database from the annual reports published by 144 financially distressed firms listed on Bursa Malaysia. The final sample excludes the companies that missing data which is 63 out of initial sample which is 144 companies for the period 2010 to 2018. This research used static model of panel data, where panel specification and diagnostic tests were done to see the relationship of different variables with leverage. The results of the analysis revealed that out of the two factors which is two factors refer to Shariah compliant firms, while only one factor refer to non-Shariah compliant firms. The results of Shariah compliant firms are liquidity and profitability appeared to be significantly associated with leverage. While the results of non-Shariah compliant firms is only liquidity appeared to be significantly associated with leverage. All factors for Model 1 (liquidity and profitability) and Model 2 (liquidity) are negatively related to the leverage. The remaining independent variables showed insignificant relationship with leverage.